Multidrug‐resistant organisms in allogeneic hematopoietic cell transplantation - Heidenreich, Daniela; Kreil, Sebastian; Nolte, Florian; Hofmann, Wolf-Karsten; Miethke, Thomas; Klein, Stefan (European journal of haematology, 2017)
Abstract: Objective multidrug-resistant organisms (MDRO) are a challenge in allogeneic hematopoietic cell transplantation (HCT). However, in the literature there is no comprehensive analysis on MDRO in HCT. In this retrospective, single-center analysis, we appraised prevalence and clinical impact of MDRO in 98 consecutive allogeneic HCT patients. Method: Prior to the conditioning (baseline) and whenever clinically indicated patients underwent a full screening for MDRO (stool and urine cultures, swabs from several body regions). Results: It turned out that 26 patients were colonized by 33 MDRO, either at baseline (n=16) or at any other time until day 100 post?transplantation. Of these 26 patients, eight developed an infection with MDRO, four of them by 4MRGN Pseudomonas aeruginosa, and three of them died MDRO-related. However, there was no significant difference between MDRO-colonized and non-colonized patients regarding overall survival (OS) and non-relapse-mortality (NRM). There was only a trend toward a higher NRM in patients already colonized by MDRO at baseline. This was due to the high NRM in multidrug-resistant P. aeruginosa-colonized patients. Conclusion: In summary, colonization with MDRO other than P. aeruginosa had no negative impact on NRM and OS. Patients colonized by multidrug-resistant P. aeruginosa had a dismal outcome. HCT of these patients should be considered with care. Screening for MDRO in the pretransplant work-up is suggested.